PENGARUH INTELLECTUAL CAPITAL DAN KINERJA SOSIAL TERHADAP KINERJA Â KEUANGAN PERUSAHAAN BUMN GO PUBLIC YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2014 - GIYARTI, (Jurnal Akuntansi AKUNESA, 2017)
The purpose of this study to analyze the influence of Intellectual Capital and Social Performance on Financial Performance. Financial performance is measured by ROE and NPM. This study uses Modified Value Added Intellectual Capital (M-VAIC) as intellectual capital measurement, which consist of Human Capital Efficiency (HCE); Structural Capital Efficiency (SCE); Relational Capital Efficiency (RCE); and Capital Employed Efficiency (CEE). Using quantitative approach and regression technique, results show that HCE and SCE significantly affect NPM. Meanwhile, SCE has negative effect on NPM, however this study fails to document the effect of RCE, CEE and Social Performance on NPM.   Keyword: Modified Value Added Intellectual Capital (M-VAIC), Net Profit Margin (NPM), Social Performance.